"WITH MY WHOLE LIVING": CHRISTIAN WOMEN'S WAYS OF WORSHIP - Foley, Mary Anne (Journal of Dharma, 2001)
I am giving Thee worship with my whole living; I am giving Thee consent with my whole willing. O God of all Gods, I am giving Thee my soul. The words of this ancient prayer suggest that Christian worship is not simply a matter of ritual; rather it involves offering all of oneself. Thus, most of this essay is concerned with some of the ways in which over the centuries Christian women have consecrated their lives to God.2 A final section will consider their participation in ritual, a significant but not exhaustive aspect of their worship.